(untitled) - The World Bank (WB) (Washington, D.C., 2010)
Earthquakes, droughts, floods, and storms are natural hazards, but unnatural disasters are the deaths and damages that result from human acts of omission and commission. Every disaster is unique, but each exposes actions by individuals and governments at different levels that, had they been different, would have resulted in fewer deaths and less damage. Prevention is possible, and this book examines what it takes to do this cost-effectively. It looks at disasters primarily through an economic lens. Economists emphasize self-interest to explain how people choose the amount of prevention, insurance, and coping. But lenses can distort as well as sharpen images, so the book also draws from other disciplines: psychology to examine how people may misperceive risks, political science to understand voting patterns, and nutrition science to see how stunting in children after a disaster impairs cognitive abilities and productivity as adults much later.
Dự báo và quản lý thảm họa
Keywords: Emergency management,Natural disasters,Thảm họa thiên nhiên,Quản lý khẩn cấp,Disasters; Economic aspects,Khía cạnh kinh tế,Economic aspects